(untitled) (International Journal of Engineering and Computer Science, 2025)
The integration of Artificial Intelligence (AI) into digital design is transforming the way users interact with technology, especially within the domain of User Experience (UX) design. Traditionally, UX design has focused on understanding human behavior, emotions, and needs to create intuitive and user-friendly interfaces. However, the rise of AI introduces a new dimension to this process—machine logic. This refers to the ability of machines to process vast amounts of data, learn from user behavior, and make intelligent decisions that influence design outcomes. As these two paradigms—human-centered design and machine-driven logic—converge, a new era of digital experience is emerging. AI can analyze user interactions in real time, predict future behavior, and automate complex design tasks, enabling designers to build more responsive, adaptive, and personalized digital products. From recommendation engines and chatbots to voice interfaces and automated design tools, AI is becoming a vital partner in the UX workflow. This paper examines the evolving relationship between UX and AI, emphasizing the benefits of their collaboration, such as improved efficiency, deeper personalization, and enhanced user engagement. It also addresses critical challenges, including ethical concerns, data privacy, and the risk of losing the human touch in design. Furthermore, the paper outlines practical methodologies for integrating AI into the UX process in ways that respect both human values and technological capabilities. By exploring this intersection, the study aims to highlight how designers and AI systems can work together to create digital experiences that are not only intelligent but also deeply meaningful and human-centered.